Evaluation of the relationship between grit and academic performance in students: a systematic review - Silva Soares, Ana Karla; Faria Rodrigues, Luiz Felipe; Ferreira Borges, Bianca; Rodrigues Neto, Tayna Schoeffel (Pensando Psicología, 2023)
The aim of the present study was to analyze, through a systematic review with students, how grit is associated with different ways of measuring academic performance. For this purpose, a search was carried out in the Scielo, PsycNET and PubMED databases with the descriptors “academic performance”, “grit” and their variations. 1470 articles were identified, 24.6% (363) from Scielo, 24.1% (355) from PsycNET and 51.1% (752) from PubMED. After excluding duplicates and applying the eligibility criteria, 25 articles were selected for full reading. Research was identified between the years 2016 (8%) and 2021 (20%), most of which were from 2020 (36%), published in English (96%), with higher education students (48%), which They used the Short Grit Scale (67%) to measure grit and GPA (average performance; 48%) to evaluate academic performance. When analyzing the articles, they were divided into four categories: positive correlation between grit and academic performance (52%), measurement instruments (40%), low relationship between grit and academic performance (4%) and did not identify a statistically significant correlation with or GPA (4%). The findings allowed us to build a general overview of the way in which the issues of grit and academic performance are being studied, considering the national and international panorama. It is likely that the absence of national research reports a gap in the research carried out on the topics jointly in our context, suggesting future studies of both a theoretical and empirical nature.